Efektivitas Beasiswa Pendidikan dalam Meningkatkan Akses Pendidikan Tinggi bagi Masyarakat Berpenghasilan Rendah di Kalimantan Timur - Muhammad Nur Madani; Naila Faradila Naila; Rizky Zakariyya Rasyad (Nusantara Innovation Journal, 2025)
The Kartu Indonesia Pintar (KIP) program has emerged as a key initiative by the Indonesian government to enhance higher education access for low-income communities. This study focuses on assessing how effective the KIP scholarship program is in helping students from economically disadvantaged backgrounds in East Kalimantan. A qualitative research method involving interviews with scholarship recipients was utilized to uncover both the advantages and challenges they encounter. The findings indicated that while the KIP scholarship motivates students to achieve academically, there are concerns regarding the accuracy of recipient targeting and the sufficiency of financial aid. Although KIP recipients emphasized the importance of this support, it often falls short of meeting their living and educational expenses, particularly for those from other regions. To improve the program, this study recommends enhancing transparency in the selection process, adjusting financial aid to better fit local needs, and conducting regular evaluations to ensure the KIP scholarship remains effective. These proposed enhancements aim to increase the program’s benefits, promote equal access to higher education, and bolster the quality of human resources in Indonesia.